Calico Joe - Grisham, John (New York : Bantam Dell, 2013)
This story, based on the Cubs and Mets 1973 season follows the divergent paths of Joe Castle, a rookie hitter for the Chicago Cubs, and Warren Tracey, a hard-throwing Mets pitcher.
Keywords: Baseball players -- Fiction; Fathers and sons -- Fiction; Life change events -- Fiction; Fiction; Sports stories